Access to and Health Outcomes of Pediatric Solid Organ Transplantation for Indigenous Children in 4 Settler-colonial Countries: A Scoping Review - Lin, Jia; Selkirk, Enid K; Siqueira, Izabelle; Beaucage, Mary; Carriere, Carmen; Dart, Allison; De Angelis, Maria; Erickson, Robin L; Ghent, Emily; Goldberg, Aviva; Hartell, David; Henderson, Randi; et al. (Transplantation, 2024)
Solid organ transplantation (SOT) is considered the optimal treatment for children with end-stage organ failure; however, increased efforts are needed to understand the gap surrounding equitable access to and health outcomes of SOT for Indigenous children. This scoping review summarizes the literature on the characteristics of access to and health outcomes of pediatric SOT among Indigenous children in the settler-colonial states of Canada, Aotearoa New Zealand, Australia, and the United States. A search was performed on MEDLINE, EMBASE, PsycINFO, and CINAHL for studies matching preestablished eligibility criteria from inception to November 2021. A preliminary gray literature search was also conducted. Twenty-four studies published between 1996 and 2021 were included. Studies addressed Indigenous pediatric populations within the United States (n = 7), Canada (n = 6), Aotearoa New Zealand (n = 5), Australia (n = 5), and Aotearoa New Zealand and Australia combined (n = 1). Findings showed that Indigenous children experienced longer time on dialysis, lower rates of preemptive and living donor kidney transplantation, and disparities in patient and graft outcomes after kidney transplantation. There were mixed findings about access to liver transplantation for Indigenous children and comparable findings for graft and patient outcomes after liver transplantation. Social determinants of health, such as geographic remoteness, lack of living donors, and traditional spiritual beliefs, may affect SOT access and outcomes for Indigenous children. Evidence gaps emphasize the need for action-based initiatives within SOT that prioritize research with and for Indigenous pediatric populations. Future research should include community-engaged methodologies, situated within local community contexts, to inform culturally safe care for Indigenous children.